A New Collection of Educational Scratch Projects Produced by Computer Science Students - Jovanov, Mile; Stankov, Emil; Ilijoski, Bojan (FCSE, 2017)
Scratch is a free educational programming language specifically designed to be convenient for students of very young age to learn programming. The course “e-Learning Systems” is an elective course for the students at our institution – Faculty of Computer Science and Engineering (FCSE) in Skopje, primarily offered to the students enrolled in the “Computer Science Education” track, in the third semester of the undergraduate studies. Starting from the current academic year (2016/17), students of this course are asked, as a project activity, to implement an educational game or story in Scratch. In this paper we present the new website we have developed for the purposes of the course, which contains the student projects developed throughout the winter semester of 2016/17, as part of the course activities. We describe the form of the student projects and the collection of projects present on the website, as well as their functionalities and application.